Affective and continuance commitment and their relations with deviant workplace behaviors in Korea - Gill, H.; Meyer, John; Lee, K.; Shin, K.; Yoon, C. (Springer New York LLC, 2011)
This study examined the nature of the relations between affective and continuance components of organizational commitment (Meyer & Allen, 1991, Human Resource Management Review, 1: 61-89) and deviant workplace behaviors (DWB; Bennett & Robinson, 2003) in a sample of 120 Korean employees and their supervisors. As expected, we found that affective commitment was negatively related, and continuance commitment was positively, albeit modestly, related to supervisor ratings of DWB. Implications for the theory and practice are discussed.